use substitution to solve the system. y=2x+14 3x-2y=-23
Replace y with y=2x+14 in the equation 3x-2y=-23, 3x - 2(2x + 14) = - 23 solve the equation we get x = -5, so y = 2(-5) + 14 = 4
Question
Updated 3/18/2014 1:42:20 AM
Rating
3
Replace y with y=2x+14 in the equation 3x-2y=-23,
3x - 2(2x + 14) = - 23
solve the equation we get x = -5, so y = 2(-5) + 14 = 4
Confirmed by jeifunk [3/18/2014 2:03:41 AM]

Questions asked by the same visitor
Solve the compound inequality. 3u+6>24 and 2u+1>7
Question
Updated 3/18/2014 1:44:07 AM
3u+6>24
3u > 24 - 6
u > 6;

2u+1>7
2u > 7 - 1
u > 3

So the solution for the compound inequality 3u+6>24 and 2u+1>7 is u > 6 (u is greater than 6)

Confirmed by jeifunk [3/18/2014 2:03:36 AM]
27,936,996
*
Get answers from Weegy and a team of really smart live experts.
S
L
P
C
Points 553 [Total 1597] Ratings 2 Comments 533 Invitations 0 Offline
S
R
L
R
P
R
P
R
R
R
R
P
R
P
Points 463 [Total 2472] Ratings 4 Comments 423 Invitations 0 Offline
S
L
Points 365 [Total 511] Ratings 1 Comments 355 Invitations 0 Offline
S
Points 30 [Total 30] Ratings 3 Comments 0 Invitations 0 Offline
S
Points 20 [Total 20] Ratings 2 Comments 0 Invitations 0 Offline
S
Points 19 [Total 19] Ratings 1 Comments 9 Invitations 0 Offline
S
L
R
P
Points 18 [Total 1381] Ratings 0 Comments 18 Invitations 0 Offline
S
Points 12 [Total 12] Ratings 0 Comments 2 Invitations 1 Offline
S
Points 12 [Total 12] Ratings 0 Comments 12 Invitations 0 Offline
S
Points 11 [Total 11] Ratings 1 Comments 1 Invitations 0 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.